Tanggap Fisiologi Akar Sorgum (Sorghum bicolor L. Moench) terhadap Cekaman Aluminium dan Deﬁ siensi Fosfor di dalam Rhizotron - Agustina, Karlin; Sopandie, Didy; Trikoesoemaningtyas, ,; Wirnas, Desta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> A study on physiological mechanism of sorghum to aluminum (Al) toxicity and phosphorous (P) deﬁ ciencies was conducted using several sorghum genotypes in rhizotron. The study was conducted in the greenhouse of the University Farm, Bogor Agricultural University from August to October 2009. The experiment was carried out as a Factorial experiment in a Completely Randomized Design with three replications. The ﬁ rst factor was sorghum genotypes consisted of Numbu (tolerant) and B-75 (sensitive), and the second factor was combination of lime and phosphorous fertilization consisted of: no lime-no P (R1), no lime-low P (R2), no lime-sufﬁ cient P (R3), lime-no P (R4), lime-low P (R5) and lime-sufﬁ cient P (R6). The results showed that all variables were signiﬁ cantly affected by the interaction of media and genotype, except for length of shoot and total P uptake. Under low P and Al toxicity, sorghum variety Numbu showed a higher nutrient efﬁ ciency than B-75 with ability of forming greater dry mass. The sensitive genotypes showed a higher nutrient uptake but a lower P nutrient use efﬁciency under Al toxicity and P deﬁ ciency. Total P uptake and P nutrient use efﬁ ciency were highly correlated with root growth and dry material accumulation. Keywords: sorghum, Al toxicity, P deﬁ ciencies, P nutrient use efﬁ ciency, P uptake